Analisis Pengaruh Pendistribusian Dana Zakat Terhadap Mustahik Ditinjau Dengan Menggunakan Metode CIBEST - Abdul Salam; Rif'atun Nisa (JESI (Jurnal Ekonomi Syariah Indonesia), 2021)
This study aims to analyze the distribution of productive zakat funds to mustahik materially and spiritually. The type of research used by researchers here uses a qualitative-quantitative approach where the population is 40 households according to the BAZNAS Yogyakarta City data in 2018, the analysis tools used are data reduction, data presentation and drawing conclusions. The results of this study indicate that the increase in the welfare level of mustahik is 53%, indicating that there is a decrease in the percentage of 37% of the community, where initially 34 out of 40 mustahik are in quadrant II (material poverty) to 20 out of 40 mustahik alone are still in material the poverty quadrant. Meanwhile, the welfare quadrant itself has increased where previously there were only 5 out of 40 households that were included in this quadrant to 19 out of 40 households, where as many as 22 mustahik who were included in quadrant II (material poverty) moved to quadrant I (prosperous)